An Exploratory Analysis of Existing Dairy Farming Practices Followed by Tribals in Madhya Pradesh State - Barela, Hari Ram; Jha, S. K.; Maiti , Sanjit; Mandi, Kalyan (International Journal of Livestock Research, 2020)
Livestock rearing happens to be an integral part of the livelihood of tribal households and to the broad rural economy since ancient times and have been contributing enormously in socio-economic development of millions of households and national economy. Integration of dairy component along with crop farming provides livelihood security to the tribal farmers. The present study was undertaken in two districts from most tribal populated area of Madhya Pradesh State (i.e. Jhabua and Dhar). From each district two blocks and from each block/tehsil two villages were selected randomly. Thus, a total of eight villages were selected and from each selected village 15 respondents were randomly selected. Overall, a total of 120 respondents were selected for the study. The salient findings of the study highlighted that, majority (53.33%) of the tribal farmers were able to identify the heat symptoms in animals by the bellowing and mounting of dairy animals, around 40 per cent fed dry fodder like maize, bajra, jowar etc. A large majority (80 %) was not vaccinating their animals against diseases like F.M.D, H.S and B.Q. and almost 60% of the respondents were practicing the knuckling method of milking. The study also suggests facilitating training and extension activities among dairy farmers to create more awareness regarding improved dairy farming practices among tribal farmer.